Identification of glutathione transferase (GST P1) inhibitors via a high-throughput screening assay and implications as alternative treatment options for breast cancers - Sarah A. P. Pereira; Jonathan Vesin; Marc Chambon; Gerardo Turcatti; M. Lúcia M. F. S. Saraiva; Paul J. Dyson (PLoS ONE, 2025)
Glutathione S-transferase P1-1 (GST P1) is an important drug target as it is implicated in drug resistance. GST P1-1 inhibitors are typically non-productive analogues of glutathione which covers broad chemical space; hence it is likely that several clinically used drugs may unknowingly act as GST P1-1 inhibitors. We developed a high-throughput screening assay for GST P1-1 and screened 5830 compounds. From the screening, 24 potent GST P1-1 inhibitors were identified and assessed for cytotoxicity in MCF-7 and MDA-MB-231 breast cancer cell lines. Ethacrynic acid (a known GST P1-1 inhibitor), ZM 39923, PRT 4165, 10058-F4, and cryptotanshinone were shown to be the most active. A competitive GST P1-1 assay was performed to identify the inhibition type of these five compounds. Another in vitro cytotoxicity experiment was conducted to explore the differences in the cytotoxicity profiles of the combinations tested. Western blot analysis was used to identify the presence of GST P1-1 in the breast cancer cell lines tested. The implications of these results concerning alternative treatment options for breast cancers are discussed.